IMPLEMENTASI BUILDING INFORMATION MODELLING MENGGUNAKAN OPENBUILDINGS DESIGNER PADA PEMBANGUNAN GEDUNG PERPUSTAKAAN DI KABUPATEN PARIAMAN - Bakar, Irma Heldwi; Kurniawan, Deddy; Yermadona, Helga (Ensiklopedia Sosial Review, 2023)
Building Information Modeling (BIM) is a technology in of Architectural Engineering and Construction (AEC) which is capable of simulating all information in a development project into a 3D model. The aim is to facilitate 3D modeling of Library Buildings in Padang Pariaman Regency with Building Information Modeling (BIM) in architectural, structural and electrical modeling using the OpenBuildings Designer software. Data collection techniques are the methods used by researchers to obtain data. As for data collection in research using secondary data. Data collection is taken by getting AutoCad data. Then from the data that has been collected, a 3D modeling is made using the OpenBuildings Designer software. From this modeling, the results of Architectural modeling are obtained starting from walls, doors, windows, Structure modeling and Electrical modeling. OpenBuildings Designer has modeling tools specific to buildings, which make it easier for users to make more informed and accurate design decisions.